Surgical Management of Pyometra Infection in a Pet Rabbit - Vahid Ganjiani; Amin Bigham-Sadegh (Iranian Journal of Veterinary Surgery, 2023)
A 3.5-year-old mixed breed pet female rabbit with a 2.3 kg weight was referred to the Veterinary Teaching Hospital of Shiraz University. The main complaint of the owner was abdominal distension. The peculiarity of the present report is that the patient had no mating or parturition antecedent according to its history. Based on diagnostic methods and clinical examination, the presence of an enlarged organ containing fluid material and occupying most of the caudal abdomen led to the provisional diagnosis of pyometra. Exploratory laparotomy was performed under general anesthesia. After the abdominal wall incision, the uterus was immediately evident and the uterine wall was over-distended and penetrated, with purulent material free in the abdominal cavity. Next, an ovariohysterectomy was performed and the abdominal incision was closed routinely. Based on a literature review, this is one of the rare reports regarding pyometra in pet rabbits.